The importance of social motivations in economic studies of the non-profit sector - Buttler, Dominik (Journal of Public Governance, 2012)
In this paper, the authors hypothesize that the motivations of volunteers should be treated as the key factor in understanding the comparative advantage of non-profit organizations in some branches of the economy. They present the inventory which might be useful for surveys of volunteers’ motivations. The research is conducted within the economic framework.